Acoustic fractal imaging using diffraction tomography - Chow, Wen Hsiang. (2008)
The beginning of this thesis embarks with a literature review of various techniques available in breast imaging. The thesis goes in to discuss about the methods employed in tackling the major setback faced in ultrasound tomography, which is a form of diffraction tomography, since the effect of diffraction are considered. This research derived a new method that is based in the fractal nature of scattering in the breast.The thesis continues with a discussion of the reconstruction algorithm used for generating tomographic images.